Insider trading, regulation and the components of the Bid-Ask Spread - Frijns, B; Gilbert, A; Tourani-Rad, A (AUT Faculty of Business, 2005)
Insiders pose a risk to providers of liquidity, who require compensation for this and consequentially widen spreads. In this paper we investigate the relationship between insider trading regulation and the cost of trading by decomposing the components of the spread before and after the enactment of strict new laws. We find a significant decrease in information asymmetry, which is mainly observed in illiquid and high prechange information asymmetry companies. Results are robust to model specification. We also see a decrease in the contribution of information asymmetry to price volatility. Overall, our results may have implications for markets with similar characteristics.
Keywords: Insider Trading Laws; Bid-Ask Spread Decomposition; Regulatory Change.